Analisis Kepatuhan Syariah (Shariah Compliance) Produk Kredit Perumahan Rakyat (KPR) dengan Akad Murabahah pada Bank Sumut Kantor Cabang Syariah Medan - Muthi’ah, Rini; Jannah, Nurul (Regress: Journal of Economics & Management, 2022)
This research is entitled Study of Sharia Compliance in Public Housing Loan Products (KPR) with Murabahah Agreement at Bank Sumut, Medan Sharia Branch Office. Shariah Compliance can simply be interpreted as a form of obedience carried out by Islamic banks in fulfilling existing sharia principles in all aspects of their operational activities. This is the difference between Islamic banks and conventional banks.People's Housing Credit (KPR) is a facility provided by banks to customers who wish to have a place to live (home). In general, mortgages in Islamic banks use a lot of murabahah contracts. Murabahah itself means a sale and purchase agreement made between two parties, namely the bank and the customer. Which is where the Islamic bank will buy the house that the customer wants and then sell it to the customer at a cost plus a profit margin that has been mutually agreed upon.The method used in this research is descriptive qualitative. Data obtained from the results of observations and documentation on the bank directly. This study aims to see how to provide Murabahah mortgage financing and the extent of sharia compliance with Murabahah mortgage products at Bank Sumut Syariah Medan Branch Office.